NATURAL RESOURCES AND THEIR USE FOR CHECKABILITY INCREASING THE DIGITAL COMPONENTS OF SAFETY-CRITICAL SYSTEMS - Drozd, Julia; Drozd, Alexander; Sulima, Julian (International Journal of Computing, 2014)
The models, methods and means as target resources for solving tasks for design and testing of computer systems and their components are considered. A criterion for choosing the target resources activating the natural resources for the increasing the efficiency of task solutions is determined. A problem of low checkability of digital components of safety-critical systems is examined and the ways of its solution is showed by choosing the target resources in accordance with the offered criterion. The way of elimination of a contradiction between the target resources aimed to maintain the checkability, productivity and low complexity of digital components is described. This way is based on parallelization of computations with the use of the serial codes.